Switchable Anisotropic/Isotropic Photon Transport in a Double-Dipole Metal-Organic Framework via Radical-Controlled Energy Transfer - Xiong, Zhile (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.